Pendidikan Kesehatan dengan Media Booklet Terhadap Perilaku Ibu dalam Melakukan Deteksi Dini Tumbuh Kembang (DDTK) pada Anak : Health Education with Booklet Media on Maternal Behavior Behavior in Conducting Early Detection of Growth and Development (DDTK) in Children - Ayuro Cumayunaro; Helda; Yonaniko Dephinto; Yelly Herien (NERS Jurnal Keperawatan, 2020)
Age of children in 1-36 months is a window of opportunity for children to learn all of the developmental aspects such as fine and gross motor skill, vision, cognitive, language skill, social development and emotional intelligence because 80% part of brain develop in this golden period. Unfortunately, some problems of child growth and development occur in this age. Early detection and intervention is very helpful for optimal growth and development. Booklet become one of effective media because it contains complete guidance, easy language, attractive appearance that can be practically carried by mothers everywhere and becomes a guide for independent detection. This research aimed to determine the effectiveness of health education with booklet to mother’s behavior (knowledge and attitude) in detecting growth and development of children 1-36 months. This research used quasi experimental design with one group pretest-posttest approach. Health education with booklet was given to 51 mothers selected by purposive sampling technique. Knowledge and attitude were measured by questionnaire and the results were analyzed by paired T test. Statistical analysis found that there is significance difference between mother’s knowledge (p=0,000) and attitude (p=0,005) in conducting early detection of child growth and development before and after health education was given. Booklet is effective media for providing health education to mothers. Health professionals can use booklet to improve mother’s knowledge and attitude so they can monitor children’s growth and development optimally.